Dalihan Na Tolu as the Philosophical Foundation of Social Relational Ethics: A Cultural Philosophy Perspective from Batak Toba Local Wisdom - Laurentius Tinambunan; Gonti Simanullang; Andre Fransiskus Malau (SEAN Institute, 2024)
Globalization, digital transformation, and increasing multicultural interaction have significantly altered patterns of social relationships, leading to the emergence of individualism, declining communal solidarity, and weakening cultural identity. These developments have encouraged scholars to reconsider local wisdom as an alternative philosophical foundation for rebuilding social ethics. Although Dalihan Na Tolu has long been recognized as the traditional kinship system of the Batak Toba community, previous studies have predominantly interpreted it from anthropological, sociological, and customary law perspectives. Consequently, its philosophical structure has not yet been systematically reconstructed within the framework of cultural philosophy. This study aims to reconstruct Dalihan Na Tolu as the philosophical foundation of social relational ethics by examining its ontological, epistemological, and axiological dimensions. This research employed a qualitative library research design using philosophical hermeneutics. Primary and secondary sources concerning cultural philosophy, Batak Toba culture, Dalihan Na Tolu, hermeneutic philosophy, and relational ethics were analyzed through hermeneutic interpretation, conceptual analysis, comparative philosophical dialogue, and theoretical synthesis. The findings demonstrate that Dalihan Na Tolu represents a comprehensive philosophical system rather than merely a customary institution. Ontologically, it conceptualizes human beings as relational beings whose identity is constituted through reciprocal social relationships. Epistemologically, cultural knowledge is constructed through tradition, symbols, language, historical experience, communal deliberation, and intergenerational interpretation. Axiologically, Dalihan Na Tolu embodies respect, responsibility, solidarity, justice, relational balance, deliberation, and peace as fundamental ethical values governing communal life. The principal contribution of this study is the formulation of the Philosophical Relational Ethics Model of Dalihan Na Tolu, an integrative framework that synthesizes relational ontology, hermeneutic epistemology, and relational axiology into a coherent model of cultural philosophy. This model extends the discourse of Indonesian cultural philosophy while demonstrating that indigenous wisdom can serve as a universal philosophical resource for strengthening social ethics within multicultural societies.